FINANCIAL PERFORMANCE COMPARISON ANALYSIS BEFORE AND AFTER THE ACQUISTION OF COMPANIES LISTED ON THE IDX FOR THE PERIOD 2016 -2021 - Mismiwati Mismiwati; Rika Lidyah; Lita Ayudha Ningsih (SEAN Institute, 2023)
This study aims to analyze the comparison of the company's financial performance three years before and three years after making acquisitions listed on the Indonesia Stock Exchange for the 2017 period. The company's financial performance is measured using financial ratios, namely, the liquidity ratio (Current Ratio), the solvency ratio (Debt to Asset Ratio), activity ratio (Total Asset Turn over), Profitability ratio (Return On Assets, Return On Equity, Net Profit Market), and market ratio (Earning Per Share). The research method used is quantitative. Meanwhile, the population of this study included public companies listed on the IDX that carried out acquisitions and companies that announced acquisition activities in the 2017 period. The sample for this study was purposive sampling. The data analysis method used in answering the hypothesis is using descriptive statistics, normality test, and different tests (Sample Paired T Test and Wilcoxon Sign Rank test). The results of hypothesis testing using the Wilcoxon Sign Rank test, namely the Current Ratio, there is a difference between before and after the acquisition and the other six ratios, namely Total Asset Turn over, Return On Assets, Return On Equity, Net Profit Market, and Earning Per Share, there is no difference between before and after the acquisition. From the results that have been stated, it can be concluded that for companies that will carry out acquisition activities, they must see how the financial performance of the company to be acquired so that there is no loss for those who will acquire the company.